Determinants of Smart–Circular Economy Integration for Quality of Life and SDG Achievement in Indonesia: A PLS-SEM Analysis - Muhammad Alfarizi; Rini Kurnia Sari; Rafialdo Arifian (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2025)
The country's economy is evolving, driven by activities that enhance income and welfare, encompassing financial aspects, technological advances, and ecosystem preservation. The circular and intelligent economies support sustainable development through resource efficiency and technology. This study examines the role of government support, Industry 4.0 resource capability, and netizen character in driving Smart Economy and Circular Economy development and their implications for quality of life and SDGs empowerment in Indonesia. The research was conducted in five leading Smart Cities—Jakarta, Bandung, Surabaya, Semarang, and Makassar—which represent regional innovation hubs in digital governance and smart development initiatives. Using a quantitative approach, data were collected from 300 respondents through structured questionnaires and analyzed using structural equation modeling (SEM-PLS). The findings reveal that Industry 4.0 resource capability and netizen character significantly contribute to Smart Economy and Circular Economy development. However, government support does not show a significant direct effect on Smart Economy development. This finding suggests that policy ineffectiveness may stem from limited inter-institutional coordination, bureaucratic fragmentation, and inconsistent implementation across regions. In contrast, Smart Economy and Circular Economy development positively influence quality of life and SDGs empowerment. The study highlights the need to prioritize policy coordination, strengthen digital infrastructure, and enhance collaborative governance to ensure more effective Smart Economy implementation. Rather than providing broad recommendations, the results emphasize improving institutional synergy and harmonizing regional policies as key strategies to address the rejected hypotheses. These findings contribute to the growing discourse on sustainable digital transformation and offer practical implications for advancing integrated Smart-Circular development at the national level. Keywords: Circular Economy, Quality of Life, Smart Economy, SDGs JEL Code: Q01, O33, H54